2021
DOI: 10.1111/sjop.12731
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of attention control in the link between multitasking with social media and academic performances among adolescents

Abstract: Prevalence of using social media services while learning, studying and doing homework is increasing rapidly among adolescents in the digital age. Although there is evidence for negative consequences of multitasking with social media, little is known about impact of social media multitasking from perspective attention control of self‐regulation. This study examined the mediating role of attention control as a component of self‐regulation in the link between social media multitasking and academic performances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…Distance learning was assessed by most respondents as less inclusive with a lower level of attention than usual. Although the research on attention span and DL is still under examination [56][57][58], it has been reported that multitasking (here defined as the ability to surf the internet and social media while in DL) has a direct effect on attention span [59] and can contribute to diminishing students' experience. The use of social media during DL requires further investigation, as uncontrolled usage of social apps can indeed produce the phenomenon of addiction, a decrement in social skills, and mental health disorders [60][61][62][63].…”
Section: Sloveniamentioning
confidence: 99%
“…Distance learning was assessed by most respondents as less inclusive with a lower level of attention than usual. Although the research on attention span and DL is still under examination [56][57][58], it has been reported that multitasking (here defined as the ability to surf the internet and social media while in DL) has a direct effect on attention span [59] and can contribute to diminishing students' experience. The use of social media during DL requires further investigation, as uncontrolled usage of social apps can indeed produce the phenomenon of addiction, a decrement in social skills, and mental health disorders [60][61][62][63].…”
Section: Sloveniamentioning
confidence: 99%
“…Nevertheless, multitasking is not necessarily detrimental to cognitive performance and may even be beneficial. Procrastination is an individual behavior with time characteristics, and the multitasking tendency reflects the preferences of the team on time usage and has certain time characteristics (Kokoç, 2021). Group team orientation can influence many studies that have confirmed the behavior of individual employees.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the efforts of employees to reduce resources for resource conservation purposes will also decrease, and the frequency of procrastination will decrease. Moreover, when individuals work in a team with a high level of cohesiveness, they can only obey the workflow in the team, and it is difficult to redistribute time resources flexibly (Kokoç, 2021). This limitation has instead exacerbated the imbalance between work requirements and individual time resources.…”
Section: The Moderating Role Of Team Cohesivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…When a result, multitasking tendency grows, work needs for employeess will increasingly surpass the employees' working hours, creating a demanding perception, namely role conflict (Mattarelli et al, 2015). Furthermore, Kokoç (2021) shows that multitasking work situations can lead to people feeling overworked. On the other hand, employees may increase their impression of resource consumption if they believe their role is overburdened.…”
Section: Polychronicity Multitasking and Role Of Conflictmentioning
confidence: 99%